Personnel selection using ELECTRE - Afshari, Ali Reza; Mojahed, Majid; Mohd Yusuff, Rosnah; Tang, Sai Hong; Ismail, Md. Yusof (Asian Network for Scientific Information, 2010)
Selecting personnel are an important problem, yet often difficult task. It is complicated because of more than one dimension. This study considers a real application of personnel selection with using the opinion of experts by one of the group decision making model, it is called ELECTRE method. This study has applied seven criteria that they are qualitative and positive for selecting the best one amongst five personnel and also ranking them. The personnel that were in the same grade in ELECTRE method were identified and were re-ranked by using AHP method. We have also used from five expert’s opinion. Finally the introduced method is used in a case study.